2023
DOI: 10.3390/ani13121970
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Probiotics Modulate Gut Barrier and Immune-Related Gene Expression and Histomorphology in Broiler Chickens under Non- and Pathogen-Challenged Conditions: A Meta-Analysis

Abstract: Data published in the literature about the favorable effects of dietary probiotics on gut health in broiler chickens are inconsistent. To obtain a more comprehensive understanding, we conducted a meta-analysis to assess the effects of probiotics on the gut barrier and immune-related gene expression, histomorphology, and growth in chickens that were either challenged or non-challenged with pathogens. From the 54 articles published between 2012 and 2022, subsets of data, separately for non-challenged and challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 99 publications
1
5
0
Order By: Relevance
“…It has been suggested that the decrease in small intestine goblet cell density may be directly or indirectly because of the EO effect on the gut microbial population ( Du and Guo, 2021 ; Hosseinzadeh et al, 2023 ). Moreover, the current results are consistent with recent studies by Danladi et al (2022) and Yosi and Metzler-Zebeli (2023) concerning the effect of PRO on the gut microstructure and improved intestinal histomorphology. It is well known that dietary PRO potentially modulates gut microbiota, regularly benefiting the bird and that GIT can adjust and modify its microstructure in response to changing situations such as diet ( Danladi et al, 2022 ; Yosi and Metzler-Zebeli, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…It has been suggested that the decrease in small intestine goblet cell density may be directly or indirectly because of the EO effect on the gut microbial population ( Du and Guo, 2021 ; Hosseinzadeh et al, 2023 ). Moreover, the current results are consistent with recent studies by Danladi et al (2022) and Yosi and Metzler-Zebeli (2023) concerning the effect of PRO on the gut microstructure and improved intestinal histomorphology. It is well known that dietary PRO potentially modulates gut microbiota, regularly benefiting the bird and that GIT can adjust and modify its microstructure in response to changing situations such as diet ( Danladi et al, 2022 ; Yosi and Metzler-Zebeli, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
“…The demand for antibiotic-free additives is now being utilized, thus the search for natural additives as an alternative to AGP has augmented research on nutraceuticals. Among these alternatives, SP, CV, EO, and PRO have enormous potential benefits because they are natural products and are free of harmful constituents and chemicals ( El-Shall et al, 2023 ; Yosi and Metzler-Zebeli, 2023 ). Therefore, the main goal of the current trial was to determine the effect of SP+CV, REO, and PRO supplementation as alternatives to AGP on growth performance, blood biochemical constitutes, meat quality, cecal microbiota, and organ histomorphology of broilers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations